Pendidikan Agama Islam Solusi Dalam Menangani Dekadensi Moral Era Milenial - Malyuna, Sita Isna Malyuna (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2024)
The research aims to explain Islamic religious education as a solution in addressing the moral decadence in the millennial era. The research method employed is qualitative, utilizing literature review. The results indicate that moral decadence in the millennial era is occurring due to the influence of the advancements in science and technology (Iptek). The development of Iptek has a significant impact, bringing about both positive and negative consequences. Despite its positive effects, the development of Iptek has also raised numerous negative issues, particularly the decline in the morality of the nation's generation (moral decadence). As a result of Iptek's progress, consumeristic, hedonistic, and secularistic attitudes are the embryos of moral decadence in the generation. This is further exacerbated when moral decadence becomes evident among the nation's young students. Threats that may be underestimated by the current generation are related to violence in the educational environment, bullying, conflicts, and sexual harassment, all of which contribute to the moral decadence of the nation. Islamic education plays a crucial role in addressing these issues. Therefore, religious education, being a strategic point in moral development, must reform and reassess its role in addressing these problems. This emphasizes the importance of revitalizing strategies for Islamic religious education to minimize the increasingly concerning moral decadence.